2005
DOI: 10.1073/pnas.0407918102
|View full text |Cite
|
Sign up to set email alerts
|

A spatially localized rhomboid protease cleaves cell surface adhesins essential for invasion by Toxoplasma

Abstract: Apicomplexan parasites cause serious human and animal diseases, the treatment of which requires identification of new therapeutic targets. Host-cell invasion culminates in the essential cleavage of parasite adhesins, and although the cleavage site for several adhesins maps within their transmembrane domains, the protease responsible for this processing has not been discovered. We have identified, cloned, and characterized the five nonmitochondrial rhomboid intramembrane proteases encoded in the recently comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
249
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(261 citation statements)
references
References 35 publications
8
249
1
3
Order By: Relevance
“…It was also shown that TgROM5 redistributes to the posterior of the parasite upon microneme secretion. This led to the conclusion that TgROM5 is responsible for MPP1 activity (Brossier et al, 2005). The discrepancy between this study and the results reported here might be explained by the use of different cell lines and constructs for the cleavage assays.…”
Section: Discussioncontrasting
confidence: 94%
“…It was also shown that TgROM5 redistributes to the posterior of the parasite upon microneme secretion. This led to the conclusion that TgROM5 is responsible for MPP1 activity (Brossier et al, 2005). The discrepancy between this study and the results reported here might be explained by the use of different cell lines and constructs for the cleavage assays.…”
Section: Discussioncontrasting
confidence: 94%
“…Apicomplexan rhomboid proteases have been implicated to play an important role in host cell invasion (10,11). PfROM1 substrates have been identified in P. falciparum by using a mammalian cell-based proteolytic assay (12) that identified various micronemal proteins as potential substrates including AMA1.…”
mentioning
confidence: 99%
“…Additional studies identified the Toxoplasma rhomboids required for key cleavage events during host cell invasion and intracellular growth (Zhou et al 2004;Brossier et al 2005Brossier et al , 2008. Similar rhomboids have been found in all other apicomplexans for which genomic sequences are available, including Cryptosporidium and Plasmodium species (Dowse and Soldati 2005), where they appear to play similar roles (O'Donnell et al 2006;Singh et al 2007).…”
Section: Rhomboidmentioning
confidence: 58%
“…Although originally recognized as a widespread mechanism of signal transduction, recent findings expand its roles to other cellular functions. In apicomplexans like T. gondii and P. falciparum, rhomboids participate in the active invasion of host cells by cleaving adhesins and are thus essential for these obligate intracellular parasites (Brossier et al 2005(Brossier et al , 2008Baker et al 2006).…”
Section: Resultsmentioning
confidence: 99%